Thermal Field Simulation of Ag Nanoparticles Induced by Femtosecond Laser. Issue 208 (12th June 2020) - Ren, Xiaoying; Li, Xiao; Wei, Fengqi; Yin, Hailong; Wen, Yonghong
Abstract: The thermal field distribution of Ag nanoparticles induced by femtosecond laser is calculated by using two-temperature equation in this paper, and its characteristics of Ag nanoparticles with single layered and multi-layered were compared and analyzed. It is found that there will be a local "hot spot" in the electromagnetic coupling region of adjacent particles, because of the electron tunneling effect and the plasma model for electron transfer, the temperature gradient in this region shows a trend of increasing at the beginning and then decreasing. The influence of the thermal field mainly comes from two aspects, one is the electromagnetic coupling of the plasmon mode, the other is the "cumulative effect" of temperature, and with the increase of irradiation time, the influence of the laser energy accumulation becomes more and more obvious on the thermal field distribution. At the same time, the results show that the smaller Ag nanoparticles will have higher temperature and temperature gradient with the same laser energy. It is also found that the electron and lattice temperature of Ag nanoparticles will reach the thermodynamic equilibrium distribution in 20 to 30 picoseconds.